Research progress of deubiquitinating enzymes in cerebral ischemia-reperfusion injury - Qin, XiaoHong; Zhu, JiangRui; Lu, HaoRan; Yi, MaoRui; Zhao, ZiLong; Zhang, WenFei; Cheng, Jing (Frontiers in Aging Neuroscience, 2025)
Cerebral ischemia-reperfusion injury (CIRI) is a critical pathological process driving neurological deterioration following ischemic stroke, involving multifaceted mechanisms such as inflammatory cascades, oxidative stress, and programmed cell death (PCD). Deubiquitinases (DUBs), as key regulators of the ubiquitin-proteasome system, dynamically modulate protein stability, signal transduction, and subcellular localization through editing the ubiquitin code, exhibiting dual roles in CIRI—both as drivers of pathogenesis and potential therapeutic targets. This review systematically elucidates the core regulatory mechanisms of DUBs in CIRI: (i) suppression of neuroinflammation via modulation of NLRP6/NF-κB pathways; (ii) mitigation of oxidative stress through the KEAP1-NRF2 axis and mitochondrial quality control; and (iii) neuroprotection by intercepting necroptosis, ferroptosis, and other PCD pathways. We further reveal that CIRI disrupts DUBs functionality through a tripartite mechanism—transcriptional dysregulation, catalytic inactivation, and subcellular mislocalization—transforming DUBs from guardians of homeostasis into mediators of injury. Consequently, DUBs-targeted strategies, including small-molecule inhibitors (e.g., IU1, Vialinin A), genetic editing approaches (e.g., BRCC3 silencing, A20 overexpression), and exosome-based delivery systems (e.g., the KLF3-AS1/miR-206/USP22 axis), demonstrate significant neuroprotective potential. However, challenges persist, such as substrate specificity, ubiquitin chain-type dependency, and barriers to clinical translation. Future research must integrate multi-omics technologies, develop brain-targeted delivery platforms, and explore synergistic effects of DUBs modulation with existing therapies to advance precision medicine in stroke treatment.